Approaches to the control of sexually transmitted infections in developing countries: old problems and modern challenges. Issue 3 (28th May 2004) - Mayaud, P; Mabey, D
Abstract : Sexually transmitted infections (STIs) constitute a huge health and economic burden for developing countries: 75–85% of the estimated 340 million annual new cases of curable STIs occur in these countries, and STIs account for 17% economic losses because of ill health. The importance of STIs has been more widely recognised since the advent of the HIV/AIDS epidemic, and there is good evidence that the control of STIs can reduce HIV transmission. The main interventions which could reduce the incidence and prevalence of STIs include primary prevention (information, education and communication campaigns, condom promotion, use of safe microbicides, and vaccines), screening and case finding among vulnerable groups (for example, pregnant women), STI case management using the syndromic approach, targeted interventions for populations at high risk (for example, sex workers), and in some circumstances (targeted) periodic mass treatment. The challenge is not just to develop new interventions, but to identify barriers to the implementation of existing tools, and to devise strategies for ensuring that effective STI control programmes are implemented in the future.